STUDY OF A THREE-AXIS PIEZORESISTIVE ACCELEROMETER WITH UNIFORM AXIAL SENSITIVITIES - Abdelkader Benichou; Nasreddine Benmoussa; Kherreddine Ghaffour (European Scientific Journal, ESJ, 2013)
Micro-electro-mechanical systems (MEMS) for automotive industry and biomedical applications (BioMEMS) have the fastest growth rate within the MEMS market. The Microsystems job market imposes to research laboratories and universities to respond by increasing the quality of MEMS engineering and informatics interdisciplinary training programs. In this fact, our work consists to study and develop a three-axis piezoresistive accelerometer having uniform sensitivities along to three axes. This sensor which is made of a heavy proof mass and four long beams, allow us to obtain high sensitivities, by reducing the resonant frequencies. Uniform axial sensitivities, with a transverse sensitivity, could be obtained using a three-axis sensor. The stress analysis of this sensor was performed in order to determine the positions of the piezoresistances, in the four flexure beams.